Analysis of methods for stabilization flow parameters of the production line - Pihnastyi, O. M. (ТОВ "Планета-Прінт", 2021)
The report discusses methods for stabilizing the flow parameters of a production line with a flow method of organizing production.
Keywords: production line; PDE-model of production